RANCANG BANGUN SISTEM INFORMASI PENJUALAN MENGGUNAKAN METODE LINEAR SEQUENCE PADA TOKO REJEKI PERKASA MOTOR PALOPO - Ferdinand Pangemanan; Sudirman; Hasniati (STMIK KHARISMA Makassar, 2019)
This study aims to develop a sales application that can help the Palopo Shop Rejeki Perkasa Motor process sales data and stock items by applying a sequential linear method so that it can support the sales activities of the store. The stages in this study are divided into five, namely analysis and definition of needs, system design and software, implementation and unit testing, integration and system testing, and operation and repair. To obtain data and information that supports the implementation of this research, an application needs analysis is carried out. System design which includes system modeling is done using DFD (Data Flow Diagram) and data modeling using ERD (Entity Relationship Diagram), then implemented using Visual studio 2013 programming language and mysql as its database.